Psychometric Properties of the Persian Version of the Brief Illness Perception Questionnaire in Chronic Diseases - Nasrin Masaeli; Reza Bagherian; Gholamreza Kheirabadi; Anahita Khedri; Behzad Mahaki (Vesnu Publications, 2020)
Introduction: The aim of this study was to evaluate the psychometric properties of Persian version of Brief Illness Perception Questionnaire (BIPQ) in three groups of chronic diseases [myocardial infarction (MI), diabetes mellitus, and multiple sclerosis (MS)]. Materials and Methods: This study was a psychometric study on 135 patients with MI, MS, or diabetes mellitus who were selected through available sampling in Isfahan City, Iran. They completed Persian versions of BIPQ, and Hospital Anxiety and Depression Score (HADS), and the World Health Organization-Brief Quality of Life (WHOQOL-BREF-26). Then, the data were analyzed. Results: The reliability of the whole questionnaire and it's subscales was between 0.59 and 0.73. The correlation coefficients between the BIPQ questionnaire and the HADS scale and the WHO-BREF-26 questionnaire showed a significant correlation. The Kaiser-Meyer-Olkin (KMO) index was 0.70, indicating the adequacy of the sample size. By using exploratory factor analysis, two main factors (the nature and the recognition of the disease-effect of disease) explained 59% of the total variance. Conclusion: The Persian version of BIPQ has relatively acceptable reliability and validity for the population of patients with chronic diseases. It can be used in clinical and psychological studies.